Looking for European Union in the World-System: a multigraph approach - Laurent Beauguitte (European Regional Science Association (ERSA), 2010)
The European Union (EU) is often considered (at least in Europe) as a key actor in a globalized world. The aim of this presentation is to check the relevance of this perception which sometimes seems too Eurocentric to be honest. We used methodological tools coming from "Social Network Analysis" (density, centrality measures, subgroups and regular equivalence) in order to produce a relevant partition of the contemporary world, and to check if an entity called "European Union" appears (or not). This multigraph analysis is based on two databases, one regarding world trade from 1967 until today (CHELEM database), the other one deals with United Nations General Assembly voting behaviour. The first step is to create blockmodels inside these valued matrices without any a priori regarding regional groups and to see if, when and how EU appears. The second step takes the EU existence for granted and compares linkage densities within this group compared to other regional groups like ASEAN or MERCOSUR. The last step is to integrate both partitions and to highlight the cores of the system. If an integrated European Union clearly appears from an economic point of view, the situation is much more contrasted from a political point of view. Despite this balanced conclusion, the relevance of these methodological tools clearly appear for both economic and political geography.
Keywords: 330; European Union; Trade; United Nations General Assembly; Voting behaviour; Word-System